O Grupo costatus de Ommatius Wiedemann (Diptera, Asilidae) no Brasil: Novos Registros e Distribuição de Ommatius costatus Rondani e Ommatius orenoquensis Bigot - Vieira, Rodrigo (EntomoBrasilis, 2015)
Os limites geográficos de quatro espécies de Ommatiinae são estendidos: Ommatius complanatus Scarbrough, 1993; Ommatius spatulatus Curran, 1928; Ommatius spinosus Scarbrough, 1993; Ommatius uncatus Scarbrough, 1993. Além disso, um espécime adicional de Ommatius didymus Scarbrough, 1993 é examinado e suas variações morfológicas são anotadas. São fornecidos ainda registros geográficos de Ommatius costatus Rondani e Ommatius orenoquensis Bigot para o Brasil. The costatus Group of Ommatius Wiedemann (Diptera, Asilidae) in Brazil: New Records and Distribution of Ommatius costatus Rondani and Ommatius orenoquensis Bigot. Abstract. The geographic ranges of four species of Ommatiinae are extended: Ommatius complanatus Scarbrough, 1993; Ommatius spatulatus Curran, 1928; Ommatius spinosus Scarbrough, 1993; Ommatius uncatus Scarbrough, 1993. Furthermore, an additional specimen of Ommatius didymus Scarbrough, 1993 is examined and their morphological variations are noted. Geographical records of Ommatius costatus Rondani, 1850 and Ommatius orenoquensis Bigot, 1876 are listed from Brazil.